Developing an index for measuring gender lens investing in organizations: the GLIMETRICS framework - Palomo-Vadillo, Maite; Ortega-Larrea, Ana-Lucia; Bordonado-Bermejo, María-Julia; De-Pablos-Heredero, Carmen (Frontiers in Psychology, 2025)
IntroductionThe objective of this article is to develop and validate a metric for assessing gender lens investing (GLI) practices within organizations. The validation of these measurement items constitutes a methodological innovation, responding to calls in the literature for the exploration of novel approaches in comparative studies.MethodsTo achieve this objective, the development of the measurement items was informed by a comprehensive literature review, and their content validation was conducted through a Delphi study.ResultsThe primary outcome of this research is the recommendation and validation of a tool designed to measure various dimensions of GLI practices, from both an academic standpoint and the perspective of expert evaluators.ImplicationsThe application of this tool is expected to facilitate the integration and generalization of diverse perspectives on GLI. As Investment Fund Agencies and companies increasingly invest in GLI initiatives, there is a growing demand for robust instruments to effectively assess their impact.